2017
DOI: 10.4103/2249-4863.214965
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among elderly population residing in urban field practice area of a tertiary care institute of Ahmedabad city, Gujarat

Abstract: Introduction:Overall improvement in the living standards of country's population is leading to longer life expectancy. To emphasize the medical and psychological difficulties faced by geriatric people is essential to know status of their quality of life (QOL).Methodology:A community-based cross-sectional study was carried out at urban field practice area of one of the teaching institutes of Ahmedabad, Gujarat. Considering the prevalence of about 7.5% of 60 years and above people sample size of 250 was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 7 publications
(12 reference statements)
0
6
0
1
Order By: Relevance
“…Former studies reported that unmarried persons were positively correlated with hypertension and had an increased mortality from cerebrovascular diseases 34–36 . Previous research assumed that married people could improve their quality of life and medication compliance in geriatric patients with chronic illnesses 3739 . We speculate that most of the middle-aged and elderly who have a spouse are emotionally more stable and eat more regularly, though further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Former studies reported that unmarried persons were positively correlated with hypertension and had an increased mortality from cerebrovascular diseases 34–36 . Previous research assumed that married people could improve their quality of life and medication compliance in geriatric patients with chronic illnesses 3739 . We speculate that most of the middle-aged and elderly who have a spouse are emotionally more stable and eat more regularly, though further study is needed.…”
Section: Discussionmentioning
confidence: 99%
“…[24][25][26] Conventionally, those with an urban residence and the economically and socially better off tend to have lower mortality and higher longevity. [27][28][29][30] India, with a population of 1.35 billion in 2018, is experiencing significant improvement in health indicators. Life expectancy at birth has increased from 58.7 years in 1990 to 68.30 years in 2015 (Registrar General of India(RGI)).…”
Section: Introductionmentioning
confidence: 99%
“…The Quality of Life indicator was used in seven studies. [ 42 43 44 45 46 47 48 ] All these referred to the term “quality of life” [ Table 5 ]. Only four studies defined it based on the WHO concept of quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…Only four studies defined it based on the WHO concept of quality of life. [ 43 46 47 48 ] For measuring quality of life, all these studies had used the World Health Organization Quality of Life – Brief Version (WHOQOL-BREF)[ 49 ] except the study by Lahariya et al . [ 50 ] This had used the Short Form – 36 (SF 36) Version 2.…”
Section: Resultsmentioning
confidence: 99%